Factors associated with household expenditure on meat: evidence from Malaysia / Yong Kang Cheah, Azira Abdul Adzis and Rabiul Islam - Yong, Kang Cheah; Abdul Adzis, Azira; Islam, Rabiul (Faculty of Business and Management, 2022)
The objective of the present study is to examine sociodemographic and household factors associated with expenditure on meat among households in Malaysia. A seemingly unrelated regression (SUR) was utilised to analyse the associations between household expenditure on fresh and processed meat, and household heads' sociodemographic and household characteristics. Compared to households headed by younger individuals, households headed by older individuals spent more on fresh meat. Households with less-educated heads spent less on fresh and processed meats than households with welleducated heads. Larger households and households headed by employed individuals spent more on processed meat compared with smaller households and households headed by unemployed individuals. Urban households spent less on fresh meat but spent more on processed meat relative to rural households. Meat consumption expenditure varies significantly across sociodemographic and household factors. Findings of the present study are useful in formulation of policy to reduce meat consumption expenditure.